Factores de riesgo familiar que influyen negativamente en el proceso de rehabilitación de los pacientes del programa unidad de adicciones del Hospital Regional docente de Trujillo 2017. - Reyes Mayta, Glenny Fiorella (2018)
The present research work was developed in 2017, with a sample of 66 patients from the Addiction Unit Program of the Regional Teaching Hospital of Trujillo, which is located in Trujillo, capital of La Libertad. The purpose of this study is to explain how family risk factors such as frequency of conflicts, poor communication, and inadequate coping skills can negatively influence the process of patient rehabilitation. This allows us to identify which situations, attitudes and behaviors of the family negatively affect the patient and that can trigger relapses in the consumption of psychoactive substances during their treatment. The methodology that was applied was based on methods such as ethnographic, inductive-deductive, statistical and synthetic-analytic that allowed to conduct a direct study with patients using techniques such as participant observation, interviews, surveys, and at the same time obtain general conclusions of the problem so that later the hypotheses are validated. The techniques and instruments used allowed to obtain qualitative as quantitative data. The results obtained in the research confirm the hypotheses, since family risk factors negatively influence the rehabilitation process of patients of the Addiction Unit Program, since there are conflicts in the family, poor communication and inadequate skills. coping favor the patient not developing a good treatment and trigger relapses